PERENCANAAN SUPPLY CHAIN MANAGEMENT (SCM) PADA PT. XYZ BANDUNG JAWA BARAT - Maun Jamaludin (Kebijakan : Jurnal Ilmu Administrasi, 2022)
Supply Chain Management plays an important role in a business run by a company. Prior to supply chain management, companies suffered a lot of losses due to product delivery estimates that sometimes did not match market demand. Now, by implementing this supply chain management, companies can reduce losses and actually earn above-average profits. In addition, the company can also connect all parties involved in the process of converting raw materials into finished goods. For this reason, the production process and distribution of goods/services produced by a company can run more effectively and efficiently.Supply chain management includes the process of determining suppliers, logistics planning, supply distribution. The purpose of the study was to determine the processSupply Chain Management plays an important role in a business run by a company. Prior to supply chain management, companies suffered a lot of losses due to product delivery estimates that sometimes did not match market demand. Now, by implementing this supply chain management, companies can reduce losses and actually earn above-average profits. In addition, the company can also connect all parties involved in the process of converting raw materials into finished goods. For this reason, the production process and distribution of goods/services produced by a company can run more effectively and efficiently.Supply chain management includes the process of determining suppliers, logistics planning, supply distribution. The purpose of the study was to determine the process of determining suppliers, planning logistics, and distributing logistics at PT. XYZ Bandung. This study uses a qualitative method that only focuses on Supply Chain Management Planning at PT. XYZ Bandung. The result of this research is that the supplier determination process at PT. XYZ Bandung in cooperation with the sole agent of the Toyota brand holder in Indonesia, namely PT. XYZ Bandung. Logistics planning at PT. XYZ Bandung is the best in terms of product quality, competitive prices, supplier company credibility, time efficiency, location efficiency, and cost efficiency. Distribution of supplies from PT. XYZ Bandung to shops cooperate in the process of selling original TOYOTA spare parts so that they can assist in the sales process. Given that the service area is widespread in West Java, the management of PT. XYZ can build a new factory in the West Java Region, this is the goal to be able to accelerate logistics services and supply in the West Java region. of determining suppliers, planning logistics, and distributing logistics at PT. XYZ Bandung. This study uses a qualitative method that only focuses on Supply Chain Management Planning at PT. XYZ Bandung. The result of this research is that the supplier determination process at PT. XYZ Bandung in cooperation with the sole agent of the Toyota brand holder in Indonesia, namely PT. XYZ Bandung. Logistics planning at PT. XYZ Bandung is the best in terms of product quality, competitive prices, supplier company credibility, time efficiency, location efficiency, and cost efficiency. Distribution of supplies from PT. XYZ Bandung to shops cooperate in the process of selling original TOYOTA spare parts so that they can assist in the sales process. Given that the service area is widespread in West Java, the management of PT. XYZ can build a new factory in the West Java Region, this is the goal to be able to accelerate logistics services and supply in the West Java region.